Recommendations on evaluating community based psychosocial programmes - Williams, Richard (Array, 2008)
This article reports the 25 recommendations made by a NATO Advanced Research Workshop on Evaluation of Community based Psychosocial Programmes in Areas Affected by War and Terrorism that took place in April 2007. It summarises the workshop’ s agreements on how evaluators should combine values, evidence and their experience, and that of programme providers, when they design and conduct their work.